The crisis of intellectual veracity in the study of religions - Ibrahim, Haslina (Future Academy, 2018)
The demand for neutrality and impartiality in the modern study of religions has challenged the role of theology in defending religious truth. As post-modernity emerged, its philosophy sought to deconstruct modern philosophy and everything under its shell. The post-modern philosophy is sceptical against the notion of objectivity and favour for relativism. Despite the increasing awareness of religious diversity, study of religions in modern and postmodern context resumes into reducing religion as human subjective experience. This paper, therefore, seeks to discuss the dilemma concerning religious truth that marked the gap between the contemporary study of religions and theology. The author alluded to the views of contemporary theologians who struggled to reform the way theology has been taught during modernity and post-modernity under the various nomenclatures; comparative theology, world theology, and global theology. Nevertheless, does the new theology embrace the passion for religious truth? Using the interpretive and the qualitative research paradigm, the paper examines the question of religious truth by referring to a selected theme under Kalam from within the Muslim, Christian, and Jewish theology. The paper supports its findings by referring to examples in the Kalam discourse that demonstrate the viability of intellection exercises and intellectual veracity in defending religious truth at this age of religious plurality